Batik pesisir pusaka Indonesia : koleksi Hartono Sumarsono - Ishwara, Helen, 1944-; Yahya, L. R. Supriyapto; Moeis, Xenia; Rambe, Arbain (Jakarta : Kepustakaan Populer Gramedia, 2011)
Catalog and descriptions of the rare batik pesisir collections of Hartono Sumarsono, an Indonesian batik collector.
Mengandungi bibliografi (mukasurat 258-259) and indeks.
Keywords: Sumarsono, Hartono, -- 1953- -- Art collections -- Catalogs; Batik -- Private collections -- Indonesia -- Catalogs; Batik -- Indonesia -- Catalogs; Textile painting -- Indonesia -- Catalogs